2008
DOI: 10.1021/ol801561b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Columnar Mesophase of Fluorescent Liquid Crystals Bearing a C2-Symmetric Chiral Core

Abstract: A chiral and fluorescent columnar mesogen prepared from chiral binaphthols is reported. This liquid crystal comprises a C2-symmetric chiral core with two staggered aromatic planes. Its hexagonal columnar (Col(h)) mesophase was characterized by appropriate physical methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…To exhibit columnar mesophases, the traditional C2-symmetry molecules may consist of a macrocyclic core [ 56 , 57 ]. Introducing a chiral core to result in helical stacking columns by modulating the intermolecular π–π interaction between molecules is another approach [ 58 ].…”
Section: Formation Of Triazine-based Lc Dendrimers By Manipulating Their Molecular Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…To exhibit columnar mesophases, the traditional C2-symmetry molecules may consist of a macrocyclic core [ 56 , 57 ]. Introducing a chiral core to result in helical stacking columns by modulating the intermolecular π–π interaction between molecules is another approach [ 58 ].…”
Section: Formation Of Triazine-based Lc Dendrimers By Manipulating Their Molecular Morphologymentioning
confidence: 99%
“…Compared with traditional disk molecu drimer 1 with a C2-symmetry having a columnar LC phase on cooling, is unusua hibit columnar mesophases, the traditional C2-symmetry molecules may consist o rocyclic core [56,57]. Introducing a chiral core to result in helical stacking colu modulating the intermolecular π-π interaction between molecules is another a [58].…”
Section: Lc Dendrimers With C2 Symmetrymentioning
confidence: 99%
“…[15] The calculated diameter (48.0 Å) of 6 where the alkyl chains are in fully stretched all-trans conformation is significantly longer than that of the intercolumnar distance (lattice parameter a) obtained from the XRD analysis, which is attributed to the high interdigitation among the soft peripheral chains in the adjacent columns. [16] Therefore, LC 6 possesses a disk-like overall molecular shape with an elliptic columnar cross section, which belongs to typical of Col s organizations (Figure S1b). All the above analysis demonstrated that 6's columns are arrayed in Col s LC mesophase with regular stacking despite the nonplanar saddle-shaped conformation (Figure 1d).…”
Section: Resultsmentioning
confidence: 95%
“…Other important examples of bioactive benzocoumarin‐type natural products are autumnariol ( II ), and alternarion ( III ) . A chiral and fluorescent columnar mesogen ( IV ) can emit fluorescent blue light and is widely used in the field of materials. In addition, cytotoxic naphthocoumarins chrysomycins A, B, C ( V ) from Streptomyces sporoverrucosus (MTCC11715) strain isolated from the soil samples collected from Jammu Hill regions were also reported .…”
Section: Introductionmentioning
confidence: 99%